Transforming the culture of teaching and learning in science: the promise of moral dilemma stories: an interpretive case study - Settelmaier, Elisabeth (Curtin University, 2003)
It has become a habit of our time to lament about the state of the world and simultaneously profess that there is not really anything we, as individuals, can do about it because there is just too much that needs fixing. In this thesis, I challenge this view on the basis that science teachers in particular are in a unique position to raise students' awareness of problematic issues in relation to the world around them by providing students with necessary knowledge. However, sound knowledge does not equate with a positive attitude, this is why I contend that providing students with factual knowledge might not be enough to enable them to participate in the public discourse on making the world a 'better place' in which to live. Given the pervading influence of science on our daily lives, this discourse necessarily includes a focus on science, scientific research and its uses. However, many science educators traditionally have taught science without addressing ethical questions. I argue that the inclusion of a discourse on ethical science-related issues into science teaching might open an avenue for science educators to offer students opportunity for practising their future engagement in the public discourse about science by learning to reflect critically and collaboratively on their attitudes, beliefs and values. This thesis presents an interpretive case study, situated in the 7th Moment of Qualitative Research, which investigated the planning and implementation of a specially designed 'Ethics in Science' curriculum, in the context of national curriculum reform in Austria. The 'Ethics in Science' curriculum was implemented in two science classes in a public senior high school in Austria by a biology teacher and a mathematics/physics teacher.The study explored the appropriateness of a science teaching approach that uses dilemma stories as a pedagogical tool for initiating individual reflection and classroom discourse on ethical issues. The study was designed as a 'bricolage', drawing from ethnography, hermeneutic-phenomenology, feminism and biographical research. Autobiography caused me to engage in critical self-reflection on my own attitudes, beliefs and values, bringing to the fore the relationship between my personal history and my own ethical sensitivities. This was helpful as a 'primer' before engaging students in the act of reflection. The use of multiple methods for data-generation served the purpose of crystallisation. Integral philosophy and critical constructivism were theoretical referents for my research on the teaching and learning. The Theory of Transformative Learning and a perspective on moral learning that combines several types of ethics served as a referent for interpreting the analysis of student learning. I have drawn on the multiple perspectives of the students, teachers and myself as the researcher. It was very important to me to maintain the participants' original voices as often as possible in order to establish 'polyvocality'. Findings indicate that the teaching approach using dilemmas led to critical thinking, in some cases to critical self-reflection, and seemed to help with initiating a classroom discourse. Overall, it appears that the dilemma teaching approach can promote rational, social and emotional learning. On the teachers' side, this type of teaching seemed to challenge the teachers' existing skills with regard to facilitation and moderation of class discussion and the self-restraint needed to avoid imposing their opinion on students.An issue for the teachers concerned their uncertainty about when to intervene in group-processes. The data-analysis also led to seemingly contradictory results which I interpreted using a dialectical 'dilemma' framework wherein the synthesis of two contradictory poles serves as a starting point for a higher level of understanding. I identified seven 'pedagogical dilemmas' - pedagogical because they are related to teaching and learning in the context of a dilemma teaching approach, and 'dilemma' because they require a choice on the side of the educator who intends to use a dilemma teaching approach. These pedagogical dilemmas were related to the dilemma stories, the individual reflection phases, the collaborative discourse phases, the ideal frequency of dilemma units, the teachers' skills, so-called problem students, and the time-requirements in relation to the dilemma units.